EU pension law / Hans van Meerten ; with contributions by Ton van den Brink [and others]. - Meerten, Hans van; Brink, Teo van den (Amsterdam University Press, 2019)
EU pension law is a relatively new and rapidly growing field. The call for a broader practical understanding of EU pension law is growing, as pension markets are increasingly internationalized. The handbook EU Pension Law discusses the most important financial EU legislation (IORP and PEPP) and non-financial legislation (such as the Charter of Fundamental Rights of the European Union) and its consequences for pensions. The book contains a collection of relevant articles and offers necessary basic knowledge. More importantly, it contains interesting practical cases, creating a unique bridge between theory and practice. Whether you are a student, a committed policymaker, an experienced market practitioner, or someone interested in European pension developments, EU Pension Law is designed for you.